Lessons on communication, development, and evaluation from a Freirean perspective. Issue 7 (2nd October 2020) - Marí Sáez, Víctor Manuel
ABSTRACT: Paulo Freire continues to be a particularly fertile source for the field of communication for development and social change, and for evaluating the communication practices of researchers and social organisations. This article discusses five key concepts (error, process, praxis, community, and curiosity) especially relevant to Freire's work in relation to other dominant communication processes. From these premises, the article draws lessons from research on these topics in Spain by comparing it with other similar international initiatives.